Numerical Investigation of Power Plant Operates with Super critical Pressure Boiler - Nasir, Kadhim Fadhil (Nahrain University College of Engineering Journal, 2015)
Numerical investigations were made of heattransfer to supercritical water flowing in a boilervertical tube. A comprehensive set of data wasobtained for pressures from 22.09 MPa to 25MPa, mass velocity 250-400 kg/m2s, the resultsare bulk temperatures from 345°C to 445°C, heatfluxes from 150 to 800 kW/m2, tube diameter was48 mm. The steady thermal model for crosssection of water wall tube was established. Heatflux and temperature of working fluid aredetermined by using Fortran computer programat each section of the tube length. The heattransfer coefficients show behavior dependingupon the heat flux. the power of plant, boilerefficiency, and plant efficiency was determined atdifferent mass velocities, we found that the boilerand plant efficiencies increasing with theincreasing of power of plant. The comparisonbetween this investigation results and the resultsof other sources, we found good agreementbetween literatures references and numericalresults of this study.